Learners satisfaction of e-learning among public university students : a case study in Kota Bharu / Nurul Bariyah Ibrahim... [et al]. - Ibrahim, Nurul Bariyah; Ibrahim, Nur Safwati; Mior Mohd Yusof, Mai Syazwani; Roslan, Nadiah Nabilah (Unit Penerbitan UiTM Kelantan, 2019)
E-learning is the learning styles that using internet to provide education information to the users according the development of technology. It also can access by using any electronic media. Nowadays, many students are often dissatisfied with the e-learning experience because the process of e-learning is less efficient than face to face learning. Therefore, a survey was conducted to identify the relationship between (learner computer anxiety, course flexibility and perceived usefulness) and perceived e-learners satisfaction and to determine the significant influence of (learner computer anxiety, course flexibility and perceived usefulness) on perceived e-learners satisfaction. A cross-sectional study with two-stage cluster sampling was applied in this study. A validated online questionnaire was distributed to 263 students from selected clusters. There are several method of data analyses was applied for this research such as Pearson's Correlation and Multiple Linear Regression. This study shows there is a positive weak linear relationship between course flexibility and perceived e-learner satisfaction. While, computer anxiety and perceived usefulness have positive moderate linear relationship towards perceived e-learner satisfaction. Factors influenced the perceived e-learners satisfaction were computer anxiety and perceived usefulness with perceived usefulness was the most influenced factor. In conclusion, since the perceived usefulness is affecting the most of the perceived e-learners satisfaction, the university management can improved e-learning system with user friendly basis to attract the e-learners to use the system for reading, downloading learning material and interacting to participate in discussion, chatting and emailing. This can improve their academic performance and allowing them to learn effectively.